2018
DOI: 10.2298/zmsdn1867345b
|View full text |Cite
|
Sign up to set email alerts
|

Socio-psychological cost of childbearing in Serbia and political response

Abstract: МИР ЈА НА БО БИЋ mbo bic@f.bg.ac.rs МИ ЛИ ЦА ВЕ СКО ВИЋ АН ЂЕЛ КО ВИЋ mzan djel@f.bg.ac.rs Уни вер зи тет у Бе о гра ду Фи ло зоф ски фа кул тет Оде ље ње со ци о ло ги је Чи ка Љу би на 18-20, Бе о град, Ср би јаСА ЖЕ ТАК: Ср би ја при па да кор пу су од ви ше од по ло ви не зе ма ља све та ко је има ју ве о ма ни ске ни вое ра ђа ња. Пре ма по да ци ма по пи са из 2011, ни јед на ге не ра ци ја же на у Ср би ји (без Ко со ва и Ме то хи је), ро ђе них жи во та и оп ште оску ди це у дру штву по лу пе ри фе ри … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, there is another contextual aspect of childbearing and parenthood in Serbia. That is persistent patriarchy, presupposing accentuated gender inequality at home, intensive motherhood, and women's enormous self-sacrifice 1 for children throughout the course of their lives (Blagojević 1997(Blagojević , 2014Babović 2020;Bobić and Vesković Anđelković 2018). Studies have showed that family has become an even more important resource in the period of post-socialist transformation in Serbia due to the massive pauperisation of the population, a sharp decrease in economic activities, 1 The terms 'sacrificing' and 'self-sacrificing' will be used in this paper in honour of our late colleague and friend, Marina Blagojević Hughson.…”
Section: Introduction: Setting the Stagementioning
confidence: 99%
“…However, there is another contextual aspect of childbearing and parenthood in Serbia. That is persistent patriarchy, presupposing accentuated gender inequality at home, intensive motherhood, and women's enormous self-sacrifice 1 for children throughout the course of their lives (Blagojević 1997(Blagojević , 2014Babović 2020;Bobić and Vesković Anđelković 2018). Studies have showed that family has become an even more important resource in the period of post-socialist transformation in Serbia due to the massive pauperisation of the population, a sharp decrease in economic activities, 1 The terms 'sacrificing' and 'self-sacrificing' will be used in this paper in honour of our late colleague and friend, Marina Blagojević Hughson.…”
Section: Introduction: Setting the Stagementioning
confidence: 99%